Obtaining Halva from A Mixture of Sunflower Seeds and Ground Sunflower Meal - Salikhanova Dilnoza; Muxtasar Ismoilova; Munisa Mamajonova; Axror Abdurakhimov; Dilafruz Sagdullaeva; Raxnamo Nazirova (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
The article explores the production and quality evaluation of halva made from sunflower seed kernels and sunflower seed meal. Various formulations were tested to determine the optimal composition based on organoleptic, nutritional, and physicochemical indicators. The results showed that halva prepared from sunflower seed kernels exhibited the best quality characteristics, including balanced sweetness, oiliness, and texture. In contrast, samples made with sunflower meal or a 50/50 mixture had a darker color and lower fat content, reducing their market appeal. The analysis of vitamin and mineral content revealed that sunflower kernel halva contained higher levels of calcium and zinc, enhancing its biological value. Overall, the optimal formulation contained 45 g of sunflower kernels, 25 g of sugar, 15 g of water, one egg, and 4 g of sesame seeds, providing a product with high nutritional and sensory quality.